(untitled) (Colombia Medica, 1993)
A field study was carried out between August 1988 and October 1989 to determine the occurrence of rabies virus (Lyssavirus) in bat populations in the municipal area of the city of Cali, Department of Valle del Cauca, Colombia. Rabies virus was investigated in brain tissue using Sellers’ staining, antibody fluorescence, and inoculation in unweaned mouse brains. A total of 1349 bats, representing 12 species of 6 families, were examined. All results of laboratory analysis for the presence of this virus were negative. However, given the climatic and socioeconomic conditions of the region and the history of rabies occurrence in bats from Cali, epidemiological surveillance for the virus should be continued for vector identification in these and other wild animals.